FEKTIFITAS PENEGAKAN HUKUM TINDAK PIDANA TAMBANG ILEGAL BERDASARKAN UNDANG-UNDANG NOMOR 3 TAHUN 2020 PERUBAHAN ATAS UNDANG-UNDANG NOMOR 4 TAHUN 2009 TENTANG PERTAMBANGAN MINERAL DAN BATUBARA DI WILAYAH HUKUM POLDA BALI - I Wayan Pariawan; Cokorda Istri Dian Laksmi Dewi (Jurnal Hukum Saraswati (JHS), 2025)
Illegal mining is an activity utilized mineral natural resources which is conducted by individuals or companies that doesn’t have permission in accordance with applicable regulations. The purpose of this research is to knowing the effectiveness of law enforcement of illegal mining crimes in the jurisdiction of the Bali Regional Police, as well as obstacles in law enforcement. This research is empirical juridical research with primary, secondary, and tertiary legal sources. The data collection in this research was carried using interview techniques, documentation studies, and observation. The data obtained was then processed qualitatively and systematically. The results of the research show that law enforcement for illegal mining crimes in the jurisdiction of the Bali Regional Police is not yet effective because many cases of illegal mining are still found every year. The obstacles faced include backups from irresponsible individuals, limited facilities and infrastructure, and a lack of legal awareness among the public.